2021
DOI: 10.1177/07482337211048168
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ENST00000414355 as a biomarker of cadmium exposure regulates DNA damage and apoptosis

Abstract: Human exposure to cadmium (Cd) may induce severe effects in different organs. Recent studies suggest that long non-coding RNAs (lncRNAs) are closely involved in the pathophysiological mechanisms of Cd-related diseases. This study evaluated the use of lncRNA (ENST00000414355) as an expression signature of Cd exposure and assessed its ability to modulate DNA damage and apoptosis by measuring the expression of ATM serine/threonine kinase (ATM) and mitochondrial membrane potential (ΔΨm) in Cd-exposed workers. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Other ncRNAs that have been affected by Cd exposure are LncRNAs. A study conducted on workers exposed to Cd found a significant positive correlation between the level of Cd in the blood and LncRNA-ENST00000414355 and serine/threonine kinase (ATM) expression and a significant negative correlation between the level of Cd in the blood and the ∆Ψm [190]. Another study reported that a maternally expressed tumor suppressor LncRNA 3 (MEG3) is significantly downregulated in BEAS-2B cells transformed with Cd [191].…”
Section: Ncrnamentioning
confidence: 99%
“…Other ncRNAs that have been affected by Cd exposure are LncRNAs. A study conducted on workers exposed to Cd found a significant positive correlation between the level of Cd in the blood and LncRNA-ENST00000414355 and serine/threonine kinase (ATM) expression and a significant negative correlation between the level of Cd in the blood and the ∆Ψm [190]. Another study reported that a maternally expressed tumor suppressor LncRNA 3 (MEG3) is significantly downregulated in BEAS-2B cells transformed with Cd [191].…”
Section: Ncrnamentioning
confidence: 99%